An Update on the Biological Activities of Euterpe edulis (Juçara) - Cardoso, Alyne Lizane; de Liz, Sheyla; Rieger, Débora Kurrle; Farah, Ana Carolina Aguiar; Kunradi Vieira, Francilene Gracieli; Altenburg de Assis, Maria Alice; Di Pietro, Patricia Faria (Planta Medica, 2018)
The palm tree Euterpe edulis, known as juçara, produces spherical and purple fruits, similar to those of the Euterpe oleracea and Euterpe precatoria palm trees, from which the common name açaí originates. Juçara fruit has been gaining prominence in the scientific world for its interesting nutritional composition, which is rich in antioxidants, and for its sustainable production model. Recently, relevant biological activities have been associated with the juçara fruit, and its use in alimentation has become an important nutritional, environmental, and economic alternative. The aim of this review is to compile recent scientific data about the phytochemical characterization and biological activities of E. edulis. A review of the literature was conducted in two electronic databases, Medline and Science Direct. The eligibility criteria were as follows: phytochemicals characterize of the E. edulis fruits and evaluate biological effects in vitro or in vivo with pulp, extract, juice, or product of juçara fruits. Investigations were excluded if they used other parts of the plant (seeds), did not assess biological activities, or have tested methodologies for compound extraction. From the identified reports, 25 articles were eligible for this study. The promotion of health benefits related to juçara fruits seems to have improved antioxidant activity in vivo, benefits to lipid and glycemic profiles, and modulation of inflammatory status in experimental studies in animals.
Keywords: Euterpe edulis; Arecaceae; juçara; açaí; biological effects; antioxidant